Dental and periodontal condition by sociodemographics in Finnish adults in 2023: cross-sectional results from the Healthy Finland Survey - Suominen, Anna Liisa; Leskinen, Anni; Saxlin, Tuomas; Palotie, Ulla; Gursoy, Ulvi Kahraman; Sipilä, Kirsi; Rautava, Jaana; Pelotomäki, Timo; Lundqvist, Annamari; Harjunmaa, Ulla (Taylor & Francis, 2026)
Objective: To obtain current information of adult’s dental and periodontal condition and contributing sociodemographic factors.
Material and methods: Clinical examinations were conducted in 2023 (n = 1,798). Enamel and dentine caries prevalences were recorded as the percentages of those having at least one tooth with enamel or dentine caries, and prevalence of periodontitis as those having at least two teeth with clinical attachment loss of ≥ 4 mm or with a probing pocket depth (PPD) of ≥ 6 mm. The numbers of teeth with enamel caries, dentine caries, and PPD (≥ 4 and ≥ 6 mm) indicated the extent of dental and periodontal disease. Sociodemographic factors included age, sex, educational level, and native language.
Results: Two-thirds of the participants had nearly full dentition. Of the dentate participants, 39% had dentine caries and 92% had enamel caries. Periodontitis was detected in 27%, teeth with PPD ≥ 4 mm in 74%, and bleeding on probing in 91% of the dentate participants. Male sex, older age, a lower educational level, and a native language other than Finnish or Swedish were significantly associated with indicators of poorer dental and periodontal conditions in this study – except for extent of enamel caries. The number of teeth affected by enamel caries was highest among younger age groups.
Conclusion: Dental caries and periodontal diseases remain significant health concern among Finnish adults, as do sociodemographic disparities. These findings underscore the importance of implementing targeted preventive interventions for the identified risk groups.